Literate in what? a redifination of literacy - Sibayan, Bonifacio P. (The RAP Journal, 2002)
In a democracy, all citizens should have an equal opportunity to rise and the present language for attaining the better life because it is the language of education, the language for getting a good job, is English. The poor should have equal access to these opportunities.